Maxillary Implant-Supported Over-Denture, Role of Attachment Selection on Treatment Success Rate: A Literature Review - Allahyari, Somayeh (Journal of Dental School, 2018)
Objectives Maxillary implant-supported over-denture is a suitable treatment where conventional denture cannot be used. Few studies are available on maxillary over-denture while more are available on mandibular over-denture with no literature referring to attachment selection in maxillary over-dentures. The objective of this literature review was to see attachment selection strategies in maxillary over-denture and its effect on success rate several successes contributing factors were noted including survival rate, marginal bone loss, soft tissue problems, fracture, and retention of maxillary over-denture. Methods This review study was conducted on available article discussing maxillary implant over-denture. An online comprehensive search was performed on PubMed, Scopus, ScienceDirect, and Google Scholar is using the following key words “implant supported over-denture” and “attachments” from 2000 to 2016, with total 78 articles being obtained. Results Studies including the attachment selection and maxillary implant over-denture were prioritized. Articles that were not peer reviewed were excluded. In total 78 articles were included for initial evaluation among which, with only 35 articles were judged as related to maxillary Over-denture topic and used for evaluation and report. Conclusion Based on the reviewed articles result, the attachments type has a profound effect on the overall success rate. The number and position of implants and corresponding soft tissue are also influenced by attachment selection